2019
DOI: 10.3390/molecules24213848
|View full text |Cite
|
Sign up to set email alerts
|

(3β,16α)-3,16-Dihydroxypregn-5-en-20-one from the Twigs of Euonymus alatus (Thunb.) Sieb. Exerts Anti-Inflammatory Effects in LPS-Stimulated RAW-264.7 Macrophages

Abstract: To discover new pharmacologically active natural products, here, we performed the phytochemical analysis of a Korean medicinal plant. Euonymus alatus (Thunb.) Sieb. is a traditional medicinal plant that has been used as a remedy for various diseases in Asian countries. In particular, the cork cambium on the twigs of E. alatus has been used to treat dysmenorrhea, tumors, diabetes, and wound. Phytochemical analysis of the methanolic extract of E. alatus twigs led to the isolation of a sterol, which was identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Studies have shown that kaemferol and its derivatives reduce cholinesterase activity, prevent microglial activation, remove amyloid fibrils, and safeguard the blood-brain barrier [45]. In LPS-stimulated RAW264.7 cells and BV2 microglia cells, triterpenes (abruslactone A and demethylregelin), caffeic acid, and chlorogenic acid extracted from EA leaves and twigs are known to contribute to anti-inflammatory effects [29,46]. In addition, it was discovered that the anti-inflammatory properties of quercetin and kaemferol in EA also inhibited inflammatory mediators, including COX-2 and nitric oxide synthase [47].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that kaemferol and its derivatives reduce cholinesterase activity, prevent microglial activation, remove amyloid fibrils, and safeguard the blood-brain barrier [45]. In LPS-stimulated RAW264.7 cells and BV2 microglia cells, triterpenes (abruslactone A and demethylregelin), caffeic acid, and chlorogenic acid extracted from EA leaves and twigs are known to contribute to anti-inflammatory effects [29,46]. In addition, it was discovered that the anti-inflammatory properties of quercetin and kaemferol in EA also inhibited inflammatory mediators, including COX-2 and nitric oxide synthase [47].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the cork cambium of its twigs and wings, known as ‘Gui-jun-woo’, has historically been attributed to various functions, including enhancing blood circulation, alleviating pain, eliminating stagnant blood, and treating dysmenorrhea in past dynasties. [ 14 , 15 , 16 , 17 , 18 , 19 ]. In the RiHuaZi BenCao, another well-known traditional Chinese medicine (TCM) classic, E. alatus was recorded as a drug with the function of modulating gynecological diseases [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the RiHuaZi BenCao, another well-known traditional Chinese medicine (TCM) classic, E. alatus was recorded as a drug with the function of modulating gynecological diseases [ 19 ]. Furthermore, recent studies have substantiated the effects of E. alatus , including its efficacy in treating rheumatoid arthritis, its immune-modulating characteristics, its benefits in managing hyperglycemia and diabetic retinopathy, along with its anti-inflammatory attributes [ 14 , 15 , 16 , 17 , 19 , 20 ]. Despite these findings, the potential impact of E. alatus on bone metabolism and bone loss remains uninvestigated.…”
Section: Introductionmentioning
confidence: 99%
“…), 59 in the form of sesquiterpenes, including sesquiterpene alkaloids, triterpenes, flavonoids, and phenolic compounds, such as β-sitosterol, aromadendrin, and alatamine. 24,60 Many compounds have been isolated from Ligusticum chuanxiong Hort, 61 including ligustilide, tetramethyl pyrazine (TMP), and ferulic acid. 25 Previous animal experiments conducted by our research group have shown that SMYZD exerts a significant effect on the treatment of dementia.…”
Section: Introductionmentioning
confidence: 99%